UPAYA MENINGKATKAN HASIL BELAJAR MENGENAL NAMA-NAMA ALLAH SWT MELALUI MEDIA QUIZIZZ PADA PEMBELAJARAN DARING - I`ing Hildah (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
AbstractThe purpose of this class action research is to find out the extent of the influence of theuse of Quizizz on student learning outcomes on the material of knowing the names of God duringa pandemic. The material focuses on 4 Asmaul Husna namely Al-Mumit (Allah Almighty), AlHayyu (Allah Almighty), Al Qayyum (Allah Almighty), and Al-Ahad (Allah Almighty). Thesubjects of the study were grade 5 students. Data in the study were obtained from observation,documentation and interviews. The data obtained are analyzed by descriptive analysis. Theresults of the study found that there was an increase in the learning outcomes of grade 5 studentson the material after action through the use of Quizizz media. In the first cycle, it is known thatthere are 50% of students whose results are lacking. Furthermore, in cycle II after the action, theresults of 100% of students were not under KKM, with details of 2 students (17%) sufficientcriteria, 6 good students (50%) and excellent criteria of 4 students or 33%.Keywords: Learning Outcomes, Names of God, Quizizz AbstrakTujuan penelitian tindakan kelas ini yaitu untuk mengetahui sejauh mana pengaruhpenggunaan Quizizz terhadap hasil belajar siswa pada materi mengenal nama-nama Allah padamasa pandemi. Materi berfokus pada 4 Asmaul Husna yaitu Al-Mumit (Allah Yang MahaMematikan), Al-Hayyu (Allah Yang Maha Hidup), Al Qayyum (Allah Maha Berdiri Sendiri), danAl-Ahad (Allah Yang Maha Esa). Subyek penelitian yaitu siswa kelas 5. Data dalam penelitiandiperoleh dari observasi, dokumentasi dan wawancara. Data yang diperoleh dianalisis dengandeskriptf. Hasil penelitian diketahui adanya peningkatan hasil belajar siswa kelas 5 pada materitersebut setelah adanya tindakan melalui pemanfaatan media Quizizz. Pada siklus I diketahui ada50% siswa yang hasilnya berkriteria kurang. Selanjutnya pada siklus II setelah adanya tindakandiperoleh hasil 100% siswa tidak ada yang di bawah KKM, dengan rincian 2 peserta didik (17%)kriteria cukup, 6 siswa baik (50%) dan kriteria sangat baik sebanyak 4 peserta didik atau 33%.Kata kunci: Hasil Belajar, Nama-Nama Allah, Quizizz